2015
DOI: 10.4103/0972-0707.157263
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effect of various additives on selected physical properties of white mineral trioxide aggregate

Abstract: Aims:This study examined the setting time, compressive strength, and pH of white mineral trioxide aggregate (MTA) mixed with various additives: Calcium chloride (CaCl2), calcium formate (CaF), disodium hydrogen orthophosphate (Na2HPO4).Materials and Methods:Group 1 (Control) was obtained by mixing MTA with distilled water. In Groups 2 and 3, MTA containing 10% CaCl2 and 20% CaF, respectively, was mixed with distilled water. In Group 4, MTA was mixed with 15% Na2HPO4. Setting time, compressive strength, and pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To overcome this drawback, a number of setting accelerators applied at different concentrations have been examined [ 6 9 10 11 12 ]. CaCl 2 is the most common setting accelerator examined as a potential additive to MTA [ 6 9 13 14 15 16 17 ]. Investigations have proven the ability of the MTA/CaCl 2 combination to achieve good sealing ability and high pH values, especially at the concentration of 10% [ 18 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this drawback, a number of setting accelerators applied at different concentrations have been examined [ 6 9 10 11 12 ]. CaCl 2 is the most common setting accelerator examined as a potential additive to MTA [ 6 9 13 14 15 16 17 ]. Investigations have proven the ability of the MTA/CaCl 2 combination to achieve good sealing ability and high pH values, especially at the concentration of 10% [ 18 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with clinical perspectives, a greater compressive strength of MTA is considered to be an important feature when this material is used as pulp capping or as a coronal restorative material when it is submitted to occlusal and mastication forces [ 56 ]. However, when MTA is used as a root-end filling material, where minimal forces are applied, a low compressive strength will not be a major clinical drawback [ 40 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al [27] showed that adding Na 2 HPO 4 significantly decreased the compressive strength values when compared to a control group (i.e., MTA + distilled water).…”
Section: Discussionmentioning
confidence: 99%